Penerapan Bimbingan Konseling Pribadi-Sosial dalam Meningkatkan Penyesuaian Sosial Mahasiswa Perantau Asal Medan di Lingkungan Budaya Minangkabau - Siti Fatimah; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to examine how the implementation of Personal-Social Guidance and Counseling can improve the social adjustment of migrant students from Medan in the Minangkabau cultural environment. The research employs a qualitative approach with interviews and observation methods involving a subject identified as SS. Data were collected through in-depth interviews and observations to identify patterns of communication barriers and the adjustment process experienced by the subject. The intervention applied used a Personal-Social Guidance and Counseling approach based on Alfred Adler’s theory to help the subject develop their social adjustment abilities. The results indicate that the problems experienced by SS are closely related to the process of adjusting to a new cultural environment, differences in communication styles, and the need to be accepted within the social environment. These conditions led to feelings of inferiority, overthinking, and withdrawal behavior that affected SS’s emotional and social well-being. Through the KOPSIN approach grounded in Alfred Adler’s theory, the counseling process helped SS understand themselves, change negative thought patterns, and develop social adjustment skills, thereby improving self-confidence and interpersonal relationships. The findings affirm that the implementation of Personal-Social Guidance and Counseling, oriented toward strengthening social interest and social courage, effectively facilitates the adjustment of migrant students in the Minangkabau cultural environment without compromising their original cultural identity.